2022
DOI: 10.5603/dk.a2022.0043
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Thyroid Hormones, Metabolic Syndrome and HOMA-IR in People with Obesity or Overweight

Abstract: Objective: In the literature the data about the relationship between thyroid hormone (TH) levels and Metabolic Syndrome (MetS) components are conflicting. Our aim was to evaluate the associations between THs and MetS as well as individual components of MetS and homeostatic model assessment of insulin resistance (HOMA-IR) in euthyroid people with obesity and overweight. Materials and methods: Adult patients who presented to Family Medicine Outpatient Clinics of a tertiary hospital between May 2019 and December … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
(44 reference statements)
2
2
0
1
Order By: Relevance
“…In older patients who are just beginning to develop type 2 diabetes, higher TSH levels may have a role in the development of insulin resistance. Furthermore, Emiroğlu et al [17] reported that participants with MetS had a considerably greater level of fT3 than those without MetS, which is consistent with the current findings. However, they did not find any significant correlation between TSH and FT4 and MetS, which contrasts with our findings.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In older patients who are just beginning to develop type 2 diabetes, higher TSH levels may have a role in the development of insulin resistance. Furthermore, Emiroğlu et al [17] reported that participants with MetS had a considerably greater level of fT3 than those without MetS, which is consistent with the current findings. However, they did not find any significant correlation between TSH and FT4 and MetS, which contrasts with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Given that a major component of metabolic syndrome is hypertension, it was expected that patients with MetS would have significantly higher blood pressure. Congruent with the present investigation, Emiroğlu et al [17] demonstrated that individuals with MetS exhibited noticeably elevated SBP and DBP in contrast to those without the condition. In keeping with the current investigation, Huo et al's [18] findings showed that the incidence of MetS rose in tandem with blood pressure increases.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…El hipotiroidismo subclínico llega a afectar hasta al 10% de la población adulta mundial (18). Estas se asocian con mayor frecuencia de enfermedad cardiovascular, diabetes mellitus 2 y aumento de la mortalidad; así como anomalías relacionadas con riesgo metabólico y niveles anormales de insulina (19). En el presente estudio, la incidencia de síndrome metabólico en los pacientes con diagnóstico de hipotiroidismo subclínico fue de un 27.66%, en un estudio realizado en Sevilla norte, España.…”
Section: Discussionunclassified
“…were measured with an enzyme-linked immunosorbent assay (ELISA) kit (DiaMetra, Milano, Italy) according to the manufacturer's instructions. Insulin resistance was assessed by calculating the HOMA-IR according to the suggested formula [30]. Serum levels of adiponectin, leptin, resistin, visfatin and omentin-1 were measured using ELISA kits (Bioassay Technology Laboratory, Shanghai Korean Biotech, Shanghai City, China).…”
Section: Biochemical Analysesmentioning
confidence: 99%